L-carnitine infusion does not alleviate lipid-induced insulin resistance and metabolic inflexibility. - Yvonne M H Bruls; Yvo J M Op den Kamp; Esther Phielix; Lucas Lindeboom; Bas Havekes; Gert Schaart; Esther Moonen-Kornips; Joachim E Wildberger; Matthijs K C Hesselink; Patrick Schrauwen; Vera B Schrauwen-Hinderling (PLoS ONE, 2020)
Background Low carnitine status may underlie the development of insulin resistance and metabolic inflexibility. Intravenous lipid infusion elevates plasma free fatty acid (FFA) concentration and is a model for simulating insulin resistance and metabolic inflexibility in healthy, insulin sensitive volunteers. Here, we hypothesized that co-infusion of L-carnitine may alleviate lipid-induced insulin resistance and metabolic inflexibility. Methods In a randomized crossover trial, eight young healthy volunteers underwent hyperinsulinemic-euglycemic clamps (40mU/m2/min) with simultaneous infusion of saline (CON), Intralipid (20%, 90mL/h) (LIPID), or Intralipid (20%, 90mL/h) combined with L-carnitine infusion (28mg/kg) (LIPID+CAR). Ten volunteers were randomized for the intervention arms (CON, LIPID and LIPID+CAR), but two dropped-out during the study. Therefore, eight volunteers participated in all three intervention arms and were included for analysis. Results L-carnitine infusion elevated plasma free carnitine availability and resulted in a more pronounced increase in plasma acetylcarnitine, short-, medium-, and long-chain acylcarnitines compared to lipid infusion, however no differences in skeletal muscle free carnitine or acetylcarnitine were found. Peripheral insulin sensitivity and metabolic flexibility were blunted upon lipid infusion compared to CON but L-carnitine infusion did not alleviate this. Conclusion Acute L-carnitine infusion could not alleviated lipid-induced insulin resistance and metabolic inflexibility and did not alter skeletal muscle carnitine availability. Possibly, lipid-induced insulin resistance may also have affected carnitine uptake and may have blunted the insulin-induced carnitine storage in muscle. Future studies are needed to investigate this.